Israeli Art Now - An Extensive Presentation Summer 1991. - Helena Rubinstein Pavillion for Contemporary Art, Tel Aviv (Tel Aviv : Tel Aviv Museum of Art, 1991)
Abramson, Larry ; Abu Shakra, Asim ; Adar, Orit ; Alnkaoua, Daniel ; Aloni, Udi ; Ayal, Avishai ; Azi, Asad ; Bar-El, Ido ; Bar-Lev, Jenifer ; Ben-Ami, Amnon ; Ben-David, Arnon ; Ben-Shaul, Anat ; Ben-Zvi, Asaf ; Berest, Dganit ; Berman Kadim, Reuven ; Borkovsky, Joshua ; Cohen Gan, Pinchas ; Dagan, Elisha ; David, Nurit ; Dominey, Drora ; Dorchin, Yaacov ; Eliasaf, Smadar ; Garbuz, Yair ; Gechtman, Gideon ; Gershuni, Moshe ; Getter, Tamar ; Geva, Tsibi ; Golombek, Isaac ; Gross, Michael ; Heiman, Michal ; Hershberg, Israel ; Jacobi, Eti ; Kadishman, Menashe ; Kantor, Zvika ; Katzenstein, Uri ; Klapisch, Liliane ; Klasmer, Gabi ; Kuperminz, Yoram ; Kupferman, Moshe ; Lavie, Raffi ; Levin, Yudith ; Levy, Pamela ; Lichtenberg-Ettinger, Bracha ; Lifshitz, Uri ; Livneh, Yitzak ; Merose, Yoram ; Mishori, Jacob ; Mizrachi, Moti ; Na'aman, Michal ; Nikel, Lea ; Nubani, Ibrahim ; Ofek, Avraham ; Pichhadze, Meir ; Primor, Sigal ; Rantzer, Philip ; Rauchwerger, Yan ; Reeb, David ; Reizman, Uri ; Romberg, Osvaldo ; Sack, Daniel ; Schwartz, Buky ; Shaul, Yuval ; Shemi, Yehiel ; Shvili, David ; Slabosky, Pesach ; Streichman, Yehezkel ; Tevet, Nahum ; Tumarkin, Igael ; Tzinovitz, Pini ; Ullman, Micha ; Wakstein, David ; Ya'acoby, Dorit ; Ziv, Neta
Israeli Art Now - An Extensive Presentation Summer 1991, Tel Aviv Museum of Art, Tel Aviv, Summer 1991
Engels
kunstcatalogus
Keywords: Israel